Estrategias de valoración ambiental de cáscara de naranja (Citrus sinensis) para el fomento de la economía circular en la parroquia Canuto - Alcívar Marcillo, Daniel Alexander (2022)
The objective of the study was to establish strategies for the environmental valuation of orange peel (Citrus sinensis) for the promotion of the circular economy based on its physicochemical and functional characterization at the Guarumal site in Canuto parish. For this purpose, a socio-environmental diagnosis was carried out where the phases of the production cycle (pruning, irrigation application, weed control, harvesting, storage and commercialization in the domestic market or for self-consumption) and the identification and quantification of impacts through the qualitative and quantitative methods; using the following techniques: interview, direct observation, documentary analysis and descriptive statistical analysis that contributed to the collection of local information. Likewise, a single sample composed of orange peel residues was collected from each farm studied and analyzed in the laboratory. As a result, it was found that the productive activities of orange cultivation at the Guarumal site do not generate highly significant environmental impacts that directly affect the abiotic and socioeconomic components. The characterization showed that the orange peel flour had 4.80% protein, 62.42% carbohydrates, 14.89% for total sugars and less than 0.1 mg/100 mg for vitamin C. According to the result of the analysis and based on the 2030 Agenda and the White Paper on Circular Economy, it was determined that the strategies proposed are linked to food, industrial, environmental, textile, chemical and bioremediation fields, contributing to goals 6, 7, 11, 12 and 15 of sustainable development.